O atendimento socioeducativo em meio aberto: a visão dos adolescentes egressos de 2013 sobre o cumprimento de medida socioeducativa em São Luís - COSTA, Erica Vanessa Ramos (2015)
This work has as main objective to analyze the MSE in an open environment in São Luis - MA from the perspective of adolescents coming of the year 2013. To this end, key categories of analysis will be developed, such as rights of children and adolescents; young offenders; adolescence; infraction. And from the above analyze the reality that appears on this theme in São Luís - MA in audience the perspective of social and educational activities developed in the Specialized Social Assistance Reference Centers - CREAS. The focus of empirical research will be in the speech of the adolescents interviewed so that you can capture the extent to which the implementation of MSE in an open environment meets the policies of the Child and Adolescent - ECA and the National Socio-Educational System - SINASE, indicators will be used SINASE provided for in order to achieve the proposed objective.